U-Pb isotope systematics and impact ages recorded by a chemically diverse population of glasses from an Apollo 14 lunar soil. (15th March 2022) - Nemchin, A.A.; Norman, M.D.; Grange, M.L.; Zeigler, R.A.; Whitehouse, M.J.; Muhling, J.R.; Merle, R.
Abstract: Glass beads formed by ejection of impact-melted lunar rocks and soils are an important component of lunar soils. These glasses range from 10′s of microns to up to a few cm in diameter and contain variable, but usually relatively low (several hundred ppb to a few ppm), quantities of U. Because Pb is a volatile element, it tends to be lost from the melts, so individual impact glasses can be dated by the U-Th-Pb isotopic systems. The presence of two additional Pb components in lunar glasses, likely linked to addition of lunar Pb to the beads during their residence on the lunar surface and from terrestrial laboratory contamination, require corrections to the data before accurate formation ages of the glasses can be determined. Here we report a U-Th-Pb isotopic and geochemical study of impact glasses from the Apollo 14 soil 14163, which documents multiple impacts into chemically diverse targets that can be linked to the main groups of rocks found on the Moon, i.e., mare basalts, highlands plagioclase-rich rocks, and KREEP (from high contents of K, REE and P) enriched rocks. The impact ages show a bimodal distribution with peaks at ∼3500–3700 Ma and <1000 Ma, similar to that obtained previously by 40 Ar- 39 Ar dating of other suites of lunar regolith glasses. Our data suggest two predominant age peaks at ∼100 Ma and ∼500 Ma, with other statistically definable clusters of ages also possible. As Pb is relatively resistant to subsolidus diffusive loss in these glasses, the age clusters probably represent primary formation ages during impact events, although processes such as preferential preservation of young glasses and impact conditions necessary for production of regolith glasses need further quantification.